Investigation of optical properties and radioactive attenuation parameters of doped tungsten oxide soda lime silica SLS waste glass - Khazaalah, Thair Hussein; Mustafa, Iskandar Shahrim; Aloraini, Dalal Abdullah; Hisam, Rosdiyana; Mohd Zaid, Mohd Hafiz; M. K., Halimah; Sayyed, M. I.; Abdul Malik, Muhammad Fadhirul Izwan; Almuqrin, Aljawhara H.; Ezra, Nabasu Seth; Naeem, Hayder Salah (Elsevier, 2022)
The optical properties and radioactive attenuation parameters of doped tungsten oxide soda-lime-silica (SLS) waste glass were investigated in the current work. A novel series of lead-free transparent glass samples were manufactured with the possibility of developing radiation-absorbing glass shielding materials. The glass composition is WO3–Bi2O3–ZnO–B2O3-SLS. A new approach was employed in the utilization of soda-lime-silica (SLS) glass as an alternative for pure silicon dioxide having 74.1% of SiO2 and other elements in it. The optical properties were investigated with the help of a UV–Visible Spectrophotometer. The results for the optical properties showed that when WO3 content is increased in the glass structure, the Urbach energy ΔE and refractive index n, increase from 0.337 to 0.431 and 2.84 to 2.94 respectively, the optical basicity Λ also increase with the increase in WO3 while the energy optical band gap Eopt registered a decrease. The metallization criterion (M) confirmed that the current glass samples are nonmetallic (insulator) because Rm/Vm < 1 which is confirmed in the condensed matter theory in the Lorentz–Lorenz equations. Moreover, the theoretical radiation shielding parameter results indicate that the linear attenuation coefficient μ and Zeff were increased with an increase in WO3. It can be seen also that the relationship between the μ and HVL is an inverse one; larger values of μ result in lesser thickness of the HVL. Whereas, as the WO3 concentration increases, the half-value layer HVL decreases. The results of this study demonstrate that the glass samples are harmless, transparent to visible light, and effective radiation shielding materials.